Transcriptome Analysis of Differentially Expressed Genes Provides Insight into Stolon Formation in Tulipa edulis - Miao, Yuanyuan; Zhu, Zaibiao; Guo, Qiaosheng; Zhu, Yunhao; Yang, Xiaohua; Sun, Yuan (Frontiers in Plant Science, 2016)
Tulipa edulis (Miq.) Baker is an important medicinal plant with a variety of anti-cancer properties. The stolon is one of the main asexual reproductive organs of T. edulis and possesses a unique morphology. To explore the molecular mechanism of stolon formation, we performed an RNA-seq analysis of the transcriptomes of stolons at three developmental stages. In the present study, 15.49 Gb of raw data were generated and assembled into 74,006 unigenes, and a total of 2,811 simple sequence repeats (SSRs) were detected in T. edulis. Among the three libraries of stolons at different developmental stages, there were 5,119 differentially expressed genes (DEGs). A functional annotation analysis based on sequence similarity queries of the GO, COG, KEGG databases showed that these DEGs were mainly involved in many physiological and biochemical processes, such as material and energy metabolism, hormone signaling, cell growth, and transcription regulation. In addition, qRT-PCR (quantitative real-time PCR) analysis revealed that the expression patterns of the DEGs were consistent with the transcriptome data, which further supported a role for the DEGs in stolon formation. This study provides novel resources for future genetic and molecular studies in T. edulis.